Multiple truncated isoforms of MAVS prevent its spontaneous aggregation in antiviral innate immune signalling - Nan Qi (Nature Portfolio, 2017)
MAVS is an essential component of the pathogen-sensing machinery, and functions by forming prion-like filaments. Here the authors show that alternatively translated forms of truncated endogenous MAVS can prevent spontaneous aggregation and degradation in cells to sustain MAVS-mediated immune signalling.